2017
DOI: 10.5415/apallergy.2017.7.1.48
|View full text |Cite
|
Sign up to set email alerts
|

Anaphylaxis caused by honey: a case report

Abstract: Honey allergy is a very rare, but serious health condition. In this study, we presented 1 patient who had anaphylaxis after the honey allergological investigation with skin prick-prick test with honey. Honey as a food has been associated to allergic reactions and as the increased consumption of honey in health food may increase the incidence of honey-related allergic reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 4 publications
0
18
0
Order By: Relevance
“…Although allergy to BV has been described, it is not frequent and the use of an allergy test allows its identification in a timely manner [86,87]. The allergy to propolis, honey, royal jelly, and pollen, although they have been described, are much less frequent [88][89][90]. The medical concept for the indication of beehive products in the treatment of OA is fundamental.…”
Section: An Integrative Visionmentioning
confidence: 99%
“…Although allergy to BV has been described, it is not frequent and the use of an allergy test allows its identification in a timely manner [86,87]. The allergy to propolis, honey, royal jelly, and pollen, although they have been described, are much less frequent [88][89][90]. The medical concept for the indication of beehive products in the treatment of OA is fundamental.…”
Section: An Integrative Visionmentioning
confidence: 99%
“…Bauer et al proposed that pharyngeal and salivary gland secretions of the bee and pollen protein contents can both cause allergic reactions to honey (5). Aguair et al performed prick to prick tests with 9 different kinds of honey to a patient with honey-induced anaphylaxis and all of them were positive which points out that some bee proteins may be the possible allergen (6). Honeybees are the most common pollinator of thyme and it was reported that patients with allergic rhinitis sensitized to pollens of a plant family might develop systemic allergic reactions after ingestion of bee pollen that contained members of the same family (7).…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion of natural sweeteners, such as honey, dried fruits, and fruit pastes, increased the energy value of bars. On the other hand, it influenced their production’s technological characteristics and conditions [ 4 , 5 ]. Differences in the composition of the individual ingredients changed the nutritional matrix, creating conditions for change in the product’s nutritional, microbiological, textural, and sensory parameters [ 6 ].…”
Section: Introductionmentioning
confidence: 99%